AL-QUR’AN DAN CYBER CRIME DI MAYANTARA STUDI ANALISIS TAFSIR TEMATIK TENTANG HATE SPEECH - M. Nuruddiin Z; Ahmad Syukron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the increasing prevalence of cybercrime in the form of hate speech in cyberspace that generates social, psychological, legal, and religious moral problems, aims to analyze Qur’anic verses related to hateful expressions, to reveal their impacts according to Qur’anic exegetes, and to formulate prevention strategies grounded in Qur’anic values by employing a qualitative library based thematic exegesis method examining verses prohibiting insult, slander, backbiting, provocation, and degradation of human dignity together with classical and contemporary interpretations, with findings indicating that hate speech is strictly forbidden because it undermines human honor and triggers social fragmentation and is conceptualized in the Qur’an through terms such as sukhriyah, istihza’, namimah, ghibah, tanabuz bi al-alqab, and lamz, while ethical principles of guarding speech, avoiding suspicion, upholding justice, and cultivating piety remain highly relevant as normative foundations for digital communication, leading to the conclusion that Qur’anic interpretation offers a comprehensive and applicable moral spiritual framework for countering hate speech in the Indonesian digital sphere.